Pembangunan Sistem Informasi Kredit Pemilikan Rumah pada Lembaga Keuangan XYZ - Billy Suherman (UNIVERSITAS KALBIS, 2022)
Economic growth in Indonesia increases housing needs. Home purchase can be done with mortgage. Mortgage is provided from a bank. XYZ Bank provides mortgage service as a step to gain new clients. Problems in this research is current application method still uses conventional methods. This research is based to produce an application that can fulfill document digitalization needs in mortgage submission including credit simulation calculator based on existing workflow. The application is developed with Agile System Development Life Cycle (SDLC). Agile focuses on adaptability and fast delivery from application result. This application is developed using OutSystems Platform. Application testing is done using functionality test. The result of this research is development method is proper, black-box testing can decide success level of development, and observation is enough for data collection.